Saving, Growth, and Investment: A Macroeconomic Analysis Using a Panel of Countries - Attanasio, Orazio P.; Picci, Lucio; Scorcu, Antonello E. (The Review of Economics and Statistics, 2000)
This paper provides a descriptive analysis of the long- and short-run correlations among saving, investment, and growth rates for 123 countries over the period 1961-94. Three results are robust across data sets and estimation methods: i) lagges saving rates are positively related to investment rates; ii) investment rates Granger cause growth rates with a negative sign; iii) growth rates Granger-cause investment with a positive sign.